PENGARUH IKLIM ORGANISASI TERHADAP MOTIVASI KERJA APARATUR BIROKRASI ( SUATU STUDI DIKANTOR WALIKOTA MANADO) - MAMANUA, RIBKA SANDI; LENGKONG, FLORENCE DAICY; ROMPAS, SONNY (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract :Organizational climate is an important factor to explain employee motivation as itrelates to job satisfaction. But, common phenomenon indicates that the organizational climate isoften not gained great attention in organizations o rgovernment bureaucracy.Relative to this,theresearch was conducted to determine the effect of organizational climate on work motivation ofpersonnel in the Office of Mayor of Manado.This study using the quantitative methods. Source of data/research respondents was 37 theofficers/employees were taken with astratified random sampling technique according to the levelof class rank of 186 civil servants of Mayor's Office in Manado City (RegionalSecretariat).Techniques of data collection using the questionnaires and assisted with theinterview guide. Technique of analyzing data used for hypothesis testing is a simple regressionanalysis/linear and simple correlation/product moment.The results showed: (1) organizational climate variable regression coefficient of the apparatuswork motivation is a positive, meaningful and significant.(2) The correlation coefficient and thepower of determination of organizational climate variables on work motivation of personnel ishigh / tight and significant.Based on the results of the statistic alanalysis be concluded that organizational climate andsignificant positive effecton the motivation of personnel working in the office of the Mayor ofManado.Based on the conclusion of the study suggested: (1) organizational climate in Manado Mayor'soffice needs to be improvedon all dimensions of the organizational climate of the structure ofthe task, relationshipreward-punishment, communicationin organizations, human resourcedevelopment personnel, equipment and facilitiesto support the implementation of tasks,as wellas the comfort of the working environments; (2) It takes a strong commitment from theleadership of the local government to create a climate of Manado City organization that iscapable of creating or improving high employee motivationof the personnel/employees.Keyword: Organizational Climate, Work Motivation